Gastroesophageal reflux disease: A risk factor for laryngeal squamous cell carcinoma and esophageal squamous cell carcinoma in the NIH‐AARP Diet and Health Study cohort. Issue 11 (22nd February 2021) - Wang, Shao‐Ming; Freedman, Neal D.; Katki, Hormuzd A.; Matthews, Charles; Graubard, Barry I.; Kahle, Lisa L.; Abnet, Christian C.
Abstract : Background: Prior studies have suggested that gastroesophageal reflux disease (GERD) may be associated with risk of squamous cancers of the larynx and esophagus; however, most of these studies have had methodological limitations or insufficient control for potential confounders. Methods: We prospectively examined the association between GERD and esophageal adenocarcinoma (EADC), esophageal squamous cell carcinoma (ESCC), and laryngeal squamous cell carcinoma (LSCC) in 490, 605 participants of the NIH‐AARP Diet and Health Study cohort who were 50‐71 years of age at baseline. Exposure to risk factors were obtained from the baseline questionnaire. GERD diagnosis was extracted among eligible participants via linkage to Medicare diagnoses codes and then multiply imputed for non–Medicare‐eligible participants. Hazard ratios (HRs) and 95% CIs of GERD were computed using Cox regression. Results: From 1995 to 2011, we accrued 931 cases of EADC, 876 cases of LSCC, and 301 cases of ESCC in this cohort and estimated multivariable‐adjusted HRs of 2.23 (95% CI, 1.72‐2.90), 1.91 (95% CI, 1.24‐2.94), and 1.99 (95% CI, 1.39‐2.84) for EADC, LSCC, and ESCC, respectively. The associations were independent of sex, smoking status, alcohol intake, and follow‐up time periods. We estimated that among the general population in the United States, 22.04% of people aged 50‐71 years suffered from GERD. Using risk factor distributions for the United States from national survey data, 16.92% of LSCC cases and 17.32% of ESCC cases among individuals aged 50‐71 years were estimated to be associated with GERD. Conclusion: GERD is a common gastrointestinal disorder, but future prospective studies are needed to replicate our findings. If replicated, they may inform clinical surveillance of GERD patients and suggest new avenues for prevention of these malignancies. Abstract : In a prospective cohort of 490, 605 patients who were followed for 16 years, patients with a history of gastroesophageal reflux disease (GERD) have a 2‐fold higher risk of laryngeal squamous cell carcinoma and esophageal squamous cell carcinoma. Moreover, an estimated 17% of these cancer cases were associated with GERD. If replicated by future prospective studies, it may inform clinical surveillance of GERD patients and provide new avenues for prevention of these malignancies.